2022
DOI: 10.1111/1440-1703.12369
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the invasive Navua sedge (Cyperus aromaticus) under competitive interaction with pasture species and simulated grazing conditions: Implication for management

Abstract: Navua sedge (Cyperus aromaticus), a perennial monocot plant native to tropical Africa, is a major weed in pasture and cropping areas in the wet tropical regions of Australia and South Pacific countries. In grazing pasture lands, rapid growth and reproduction of unpalatable Navua sedge leads to displacement of co-occurring pasture species and depletion of livestock carrying capacity and production. Understanding the interspecific competitive ability of Navua sedge with co-occurring desirable grasses and in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…This means that having faster canopy development due to its leaf shape and biomass gives lablab a competitive advantage compared to other broadleaf species and may explain the poor performance seen by stylo. Previous studies have found that Rhodes grass was more competitive than humidicola against Navua sedge [15,24], and similar results were observed in our study. This suggests that the difference in growth characteristics, such as the rate of development amongst grass pasture species, may substantially impact their competitive intensity.…”
Section: Trial 1 Morphological Performance Of 14 Pasture Speciessupporting
confidence: 93%
See 3 more Smart Citations
“…This means that having faster canopy development due to its leaf shape and biomass gives lablab a competitive advantage compared to other broadleaf species and may explain the poor performance seen by stylo. Previous studies have found that Rhodes grass was more competitive than humidicola against Navua sedge [15,24], and similar results were observed in our study. This suggests that the difference in growth characteristics, such as the rate of development amongst grass pasture species, may substantially impact their competitive intensity.…”
Section: Trial 1 Morphological Performance Of 14 Pasture Speciessupporting
confidence: 93%
“…There was a total of 15 Four to five seeds of Navua sedge were planted (October 2021) in the center of a 24 cm diameter pot and thinned to one plant after emergence. The pasture species were planted simultaneously surrounding the Navua sedge at a distance of 11 cm and a density of four plants per pot (88 plants/m 2 ).…”
Section: Trial 1 Morphological Performance Of 14 Pasture Speciesmentioning
confidence: 99%
See 2 more Smart Citations